The Influence of Teaching Vocabulary by Using Picture - Hanik Nuzulimah (IAIN Salatiga, 2008)
This paper attempts to explore whether there is significant difference of achievement in vocabulary between students taught by using pictures and those are not. The subject of this study is the first year students of SLTP Muhammadiyah Simo Susukan, Semarang where the sample contains 50 students that is divided into experimental group (with treatment) and control group (without treatment). The data is gathered from participants’ score obtained from pre test and post test. Using t test as technique of data analysis, result shows that students taught by using pictures perform better than those are not. It means that there is significant difference between the two groups. Keywords: Vocabulary Teaching; Picture